2014
DOI: 10.1063/1.4891244
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic SiOx-based unipolar resistive switching memory. II. Thermal effects on charge transport and characterization of multilevel programing

Abstract: Multilevel programing and charge transport characteristics of intrinsic SiOx-based resistive switching memory are investigated using TaN/SiOx/n++Si (MIS) and TiW/SiOx/TiW (MIM) device structures. Current transport characteristics of high- and low-resistance states (HRS and LRS) are studied in both device structures during multilevel operation. Analysis of device thermal response demonstrates that the effective electron energy barrier is strongly dependent on the resistance of the programed state, with estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 55 publications
7
76
0
Order By: Relevance
“…Only encapsulated bulk devices were able to switch in air. While the presence of a SiO x edge has often been considered necessary for SiO x -based devices to electroform and switch, 14,15 these results demonstrate that this is not the case. The reason why encapsulated edge devices fail to switch in air may be related to the detailed structure of the edge.…”
mentioning
confidence: 51%
“…Only encapsulated bulk devices were able to switch in air. While the presence of a SiO x edge has often been considered necessary for SiO x -based devices to electroform and switch, 14,15 these results demonstrate that this is not the case. The reason why encapsulated edge devices fail to switch in air may be related to the detailed structure of the edge.…”
mentioning
confidence: 51%
“…Although the state's stability still needs to be improved (no equal split of resistance states), the retention reliability test demonstrates ` operation by using different SET voltages, and no degradation is observed for more than 10 3 s, thus confirming the stable, nonvolatile nature of the SiO x -based 1D-1R devices. In recent studies, a possible proton exchange model consistent with the observed resistive switching I-V response has been proposed, as shown in Figure 2f [59,60]. Several studies have used transmission electron microscopy (TEM) to document the presence of Si nanocrystals within the CF [43,61,62], but it is not yet clear whether resistive switching (RS) is the result of an overall increase in nanocrystal size or whether switching occurs in "GAP" regions in between nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…Adding a proton to Si-H-Si forms the nonconductive (SiH) 2 defect and proton desorption from (SiH) 2 reforms Si-H-Si, which are wellunderstood electrochemical reactions that could enable localized switching without incorporating ion diffusion or drift mechanisms into the model. The SET transition voltage from HRS to LRS occurs at ~2.5 V in the I-V response, and is very near the activation energy for proton desorption from SiH (~2.5 eV), thus making the defect transformation from (SiH) 2 to Si-H-Si a logical assignment for the SET transition [59,60]. In this model, the proton that is lost from (SiH) 2 reacts electrochemically with (SiOH) 2 , which is simply chemisorbed H 2 O, to form the fixed positive charged H 3 O + defect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations